DEVELOPMENT OF MESALAZINE MICROSPHERES FOR COLON TARGETING - Rajesh, Katta; Deveswaran, R.; Bharath, S.; Basavaraj, B. V. (International Journal of Applied Pharmaceutics, 2017)
Objective: The present work was aimed at preparation of mesalazine microspheres by a non-aqueous solvent evaporation method using eudragit S 100 and eudragit L 100 as pH dependent polymers for colon targeting. Methods: The ratio of drug to polymer was varied and the effect of formulation variables revolutions per minute (RPM) (1000, 1500, 2000 and 2500) and concentration of span 80 (1%, 1.5%, 2% and 2.5%) were studied. Prepared microspheres were evaluated for particle size, percent drug entrapment, granular analysis, in vitro drug release studies, Fourier transformed infrared spectroscopy (FT-IR) Differential Scanning Calorimetry (DSC), X-ray diffraction (XRD) and scanning electron microscopy (SEM) studies. Results: Particle size has decreased and percent drug entrapment had increased with increase in RPM in all formulations. When the span 80 concentration increased, the particle size of the microsphere formulations increased and percent drug entrapment decreased in eudragit S 100 microspheres; whereas in eudragit L 100 microspheres, as the concentration of span 80 increased, the particle size of the microsphere formulations decreased. The prepared microspheres sustained the drug release over a period of 12 h. Conclusion: Thus eudragit S 100 and eudragit L 100 microspheres could constitute a promising approach for colon-specific and sustained delivery of mesalazine for the treatment of inflammatory bowel disease.